Operating channel temperature in GaN HEMTs: DC versus RF accelerated life testing. Issue 12 (December 2015) - Pomeroy, J.W.; Uren, M.J.; Lambert, B.; Kuball, M.
Abstract: Channel temperature is a key parameter for accelerated life testing in GaN HEMTs. It is assumed that self-heating is similar in RF and DC operations and that DC test results can be applied to RF operation. We investigate whether this assumption is valid by using an experimentally calibrated, combined electrical and thermal model to simulate Joule heating during RF operation and compare this to DC self-heating at same power dissipation. Two cases are examined and the implications for accelerated life testing are discussed: typical (30 V) and high (100 V) drain voltages. Highlights: The validity of comparing DC and RF HTOL test results is a key issue in reliability testing. We investigate whether DC and RF self heating, and therefore channel temperature, are equivalent. For this purpose, an experimentally validated electrothermal model has been developed. Channel temperature is found to be equivalent during RF and DC operation at typical operating voltages.